10 Busy Brooms - Gerber, Carole; Fleming, Michael, 1969- (New York : Doubleday Books for Young Readers, 2016)
Little witches soar the sky in this cumulative Halloween counting book.
new kids book 2025 fall.
Keywords: Stories in rhyme; Counting; Cumulative tales; Picture books; Witches -- Fiction; Halloween -- Fiction